Student teachers’ reflections on their practices of Curriculum and Assessment Policy Statement - Khoza, Simon Bheki (South African Journal of Higher Education, 2016)
This article presents a case study of twenty two university postgraduate students (student teachers) who specialised in Curriculum Studies. The students’ projects analysis, one-on-one semi-structured interview and focus group discussion were used for data generation/production. The study concluded that student teachers were not aware of the theories that underpin their subjects CAPSs. As a result of not understanding the theories that shape their learning, they decided to continue with the way they had been working throughout their years of teaching. This suggests that they are teaching without prioritising the implementation of their subjects’ CAPSs. Purposive and convenience samplings were used in selecting the most accessible twenty-two students. This article consequently recommends the identification of theories that underpin CAPS and the curriculum type before implementation in order for teachers to understand the implementation process. Keywords: Activities, learners, objectives, outcomes, reflections, theories.